2021
DOI: 10.1021/acs.jafc.1c01088
|View full text |Cite
|
Sign up to set email alerts
|

d-Glucose Isomerization with PAMAM Dendrimers as Environmentally Friendly Catalysts

Abstract: The isomerization of D-glucose to D-fructose plays a key role in the biochemical and chemical conversion of biomass, and it is therefore desirable to develop and improve catalysts for this reaction. In this study, the environmentally friendly polymer poly(amidoamine) (PAMAM) dendrimer's properties as catalysts for this isomerization are investigated. The experimental results showed that the PAMAM dendrimers, which have basic terminal groups, can effectively promote the D-glucose isomerization reaction. Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Solvent composition has been shown to significantly affect the reaction process, and a rational design on solvent composition can increase the catalytic activity through lowering the reaction energy barrier and improving reaction rates. [57] Song et al [58] investigated the solvent effect of GVL on the generation of HMF from glucose. They found that the addition of GVL into H 2 O could significantly regulate the reaction rate, and distinct decreases in isomerization rate constants and increases in dehydration rate constants could be observed even in 1 % GVL/ H 2 O, as shown in Figure 5.…”
Section: Composition Design Of Intrinsic Solvent Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent composition has been shown to significantly affect the reaction process, and a rational design on solvent composition can increase the catalytic activity through lowering the reaction energy barrier and improving reaction rates. [57] Song et al [58] investigated the solvent effect of GVL on the generation of HMF from glucose. They found that the addition of GVL into H 2 O could significantly regulate the reaction rate, and distinct decreases in isomerization rate constants and increases in dehydration rate constants could be observed even in 1 % GVL/ H 2 O, as shown in Figure 5.…”
Section: Composition Design Of Intrinsic Solvent Systemmentioning
confidence: 99%
“…Solvent composition has been shown to significantly affect the reaction process, and a rational design on solvent composition can increase the catalytic activity through lowering the reaction energy barrier and improving reaction rates [57] . Song et al [58] .…”
Section: Effects Of Solvent System On Reaction Regulationmentioning
confidence: 99%
“…15 Solid bases 16 and solid Lewis acids 17 exhibit comparable catalytic activity for the isomerization though the Lewis acids catalyze co-formation of d -mannose in somewhat higher amounts. A broad range of solid bases exhibit catalytic activity for the isomerization, which includes MgO 14,18,19 and other alkaline earth metal (hydr)oxides, 20 MgO-doped ordered mesoporous carbon, 21 Mg–Al hydrotalcites, 14,15,18,22–30 Mg- or Ca-impregnated or exchanged zeolites, 31–35 attapulgite, 36,37 MgO–Nb phosphate, 38 Mg-doped carbon nitride, 39 Mg-containing titanosilicates, 40 CaO–ZrO 2 , 41 MgO–ZrO 2 , 42 MgO/biochar, 43 CaO–Al 2 O 3 , 44 CaO–MgO, 45 CaO/C, 46 alkaline earth metal titanates, 47 soluble amines 48–58 and N-containing solid catalysts, 50,51,54,55,59–63 silicates, 64 SiO 2 treated with ammonia, 65 zirconium carbonate, 66 ZrO 2 67 and basic hybrid catalysts. 68 Nevertheless, establishing structure–activity and structure-selectivity correlations between the textural properties of materials and their catalytic performance remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Under optimized reaction conditions, D-fructose was generated with a maximum fructose yield of 20 %. [25] Amidoximated polyacrylonitrile with an amidoxime functional group was also used as an active heterogeneous catalyst for the isomerization of glucose to fructose. [26] Besides these organic bases, inorganic bases were used in the isomerization of glucose as well.…”
Section: Introductionmentioning
confidence: 99%
“…The poly(amidoamine) dendrimers, which have basic terminal groups, can also effectively promote the isomerization reaction of glucose. Under optimized reaction conditions, D‐fructose was generated with a maximum fructose yield of 20 % [25] . Amidoximated polyacrylonitrile with an amidoxime functional group was also used as an active heterogeneous catalyst for the isomerization of glucose to fructose [26] .…”
Section: Introductionmentioning
confidence: 99%